Letter : Spanish seamen - Reed, George
025a-0106-001 Telegraphic Address: "SEAROVING LAMB LONDON" Telephone No. WATerloo 5906 (four lines) National Union of Seamen Registered Trade Union No 1493 Approved society certificate No 128 (Formerly National Sailors & Firemens Union) Founder The late J. HAVELOCK WILSON C.H., C.B.E. General Secretary W.R. SPENCE C.B.E. General Treasurer: J.B. WILSON Asst General Secretary: G REED Please quote in reply: Your ref. HVT/FC/456. Our ref. GR/MLA. ALL COMMUNICATIONS MUST BE ADDRESSED TO THE GENERAL SECRETARY. Registered Office ST GEORGES HALL, WESTMINSTER BRIDGE ROAD, LONDON, S.E.1. Mr. H.V. Tewson, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. April 28th 1939, Dear Sir, SPANISH SEAMEN. With reference to your letter of the 27th instant, I note what you say. As indicated in a previous letter I am prepared to continue to adminster the fund on behalf of the Unions concerned who are dealing with the Spanish refugee seamen problem for a further two weeks. I propose to let you have the accounts paid up to the 29th instant in connection with this matter, early next week. I am making enquiries with regard to possible accommodation in London to provide for 250 Spanish refugee seamen, and I believe, I shall be able to let you have some information with regard to this matter in the course of a few days. I think it would be to our mutual advantage to wait until we get all these Spanish seamen in London, and then they can be dealt with by a local interpreter who can secure a list of the men who desire to go to Mexico or wherever it is possible to find a final home for these people. Yorus faithfully, Geo. Reed Assistant General Secretary. 292/946/25a/106